Unraveling the compensatory mechanism: pay to play in freemium mobile games / Wong Hui Shein, Tan Chiang Ching and Wong Kee Hook - Hui Shein, Wong; Chiang Ching, Tan; Kee Hook, Wong (2023)
The freemium business model has gained popularity in the past decade, particularly in online retails. This model involves a free primary service with money made through supplemental goods and premium services. The freemium model is particularly popular in the gaming sector, with most downloadable applications using this model. This paper investigate the factors influencing adoption of Pay to Play (P2P) practices among mobile gamers in Sarawak. An online questionnaire was utilized to collect data for this quantitative study. Purposive sampling was used to choose 360 mobile players in Sarawak. This study takes into account seven different Pay to Play (P2P) concepts: social interaction, fun, challenge, diversion, fantasy, intention to play free mobile games, and desire to spend real money on virtual products. AMOS software was employed in structural equation modelling (SEM) in this study to evaluate the hypotheses. The results shows that (1) male gamers is more motive in the five variables and exhibit more play and payment intentions than female gamers, (2) social interaction, fun, diversion and fantasy are significant towards the intention to play, (3) intention to play freemium games has positive effect on the intention to pay for virtual items, (4) intention to play freemium games partially mediates the relationship between social interaction, fun, and fantasy with the intention to pay for virtual items, (5) diversion has the opposite effect on the intention to pay for the virtual items. This study has few limitations, including an uneven distribution of ethnic backgrounds among respondents, a significant portion of the respondents being students whose gaming expenses depend on parental support, and potential biases in the assessment of respondents' willingness to pay for virtual goods. This study provides valuable insights for game developers on the future of freemium gaming. It explores five P2P practices: social interaction, fun, challenge, diversion, and fantasy. It highlights that games that encourage social interaction and fun, diversion, and fantasy are more popular among gamers. The study also emphasizes the importance of designing challenges strategically to align with gamers' preferences and behaviors, potentially reshaping game development. The purpose of this study is to fill in the knowledge gaps and learn more about the impact of P2P ideas (social interaction, fun, challenge, diversion, and fantasy) on the intention to play and pay since this topic has not received as much attention in other studies. Also included in this study is the topic of compensatory consumption, which is a second area of discussion. The compensatory consumption idea is indirectly quantified by taking into account various P2P-related game components. Third, there is a lack of Sarawakian players in the literature on gaming. There is barely any research explaining game conduct among Sarawak freemium mobile gamers. Given the importance of the games market in the current environment, it is essential to conduct this research in order to better understand the factors that affect the behaviour of the gaming community in the Sarawakian market, specifically with regard to their intention to play freemium games and pay for in-game virtual goods.